2019
DOI: 10.3390/cells8050477
|View full text |Cite
|
Sign up to set email alerts
|

A Novel lnc-RNA, Named lnc-ORA, Is Identified by RNA-Seq Analysis, and Its Knockdown Inhibits Adipogenesis by Regulating the PI3K/AKT/mTOR Signaling Pathway

Abstract: Obesity is closely associated with numerous adipogenic regulatory factors, including coding and non-coding genes. Long noncoding RNAs (lncRNAs) play a major role in adipogenesis. However, differential expression profiles of lncRNAs in inguinal white adipose tissue (iWAT) between wild-type (WT) and ob/ob mice, as well as their roles in adipogenesis, are not well understood. Here, a total of 2809 lncRNAs were detected in the iWAT of WT and ob/ob mice by RNA-Sequencing (RNA-Seq), including 248 novel lncRNAs. Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 53 publications
5
36
0
Order By: Relevance
“…Numerous studies have revealed the crucial function of the PI3K/AKT signaling cascade during adipogenesis (35)(36)(37)(38)(39). For example, the PI3K/AKT signaling pathway mediated by insulin may result in excessive lipids in adipose tissue, so it serves a crucial function in the adipose cells of patients with obesity (40). A previous study revealed that IGF-1 upregulated the phosphorylation of AKT through the IGF-1R-PI3K signaling pathway, which ultimately induced the differentiation of HemScs into adipocytes (6).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have revealed the crucial function of the PI3K/AKT signaling cascade during adipogenesis (35)(36)(37)(38)(39). For example, the PI3K/AKT signaling pathway mediated by insulin may result in excessive lipids in adipose tissue, so it serves a crucial function in the adipose cells of patients with obesity (40). A previous study revealed that IGF-1 upregulated the phosphorylation of AKT through the IGF-1R-PI3K signaling pathway, which ultimately induced the differentiation of HemScs into adipocytes (6).…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG pathway enrichment analysis of target genes revealed a total of 47 annotated pathways (Additional le 7: Table S7B), of these pathways, three were signi cantly enriched (P<0.05), namely Tight junction(ko04530), Glycosaminoglycan biosynthesisheparan sulfate/heparin(ko00534) and Lysosome(ko04142). Although some pathways were not signi cantly enriched, such as Wnt signaling pathway(ko04310), AMPK signaling pathway(ko04152), mTOR signaling pathway(ko04150), Cell adhesion molecules (CAMs)(ko04514) and MAPK signaling pathway(ko04010) and Jak-STAT signaling pathway , these pathways have been reported in the literature to play an important role in lipid deposition [36][37][38][39][40][41]. Overall, the signi cantly enriched pathways and GO terms involve 49 target genes.…”
Section: Comprehensive Analysis Of Candidate Lncrnas and Mrnasmentioning
confidence: 92%
“…Among them, eight pathways were related to lipid deposition and metabolism, including alpha-Linolenic acid metabolism (ko00592), FoxO signaling pathway (ko04068), Biosynthesis of unsaturated fatty acids (ko01040), Cell adhesion molecules (ko04514), Phosphonate and phosphinate metabolism (ko00440), Ether lipid metabolism (ko00565), Tight junction (ko04530) and Arachidonic acid metabolism (ko00590). Although some pathways were not signi cantly enriched, such as PPAR, Wnt, AMPK and mTOR signaling pathways, these pathways still played an important role in lipid deposition [31,[34][35][36]. Overall, the KEGG enrichment analysis of target genes revealed 16 critical pathways with 17 target genes (Table 3).…”
Section: Comprehensive Analysis Of Candidate Lncrnas and Mrnasmentioning
confidence: 99%